Arbitrary optical wavefront shaping via spin-to-orbit coupling. (21st November 2016) - Larocque, Hugo; Gagnon-Bischoff, Jérémie; Bouchard, Frédéric; Fickler, Robert; Upham, Jeremy; Boyd, Robert W; Karimi, Ebrahim
Abstract: Converting spin angular momentum to orbital angular momentum has been shown to be a practical and efficient method for generating optical beams carrying orbital angular momentum and possessing a space-varying polarized field. Here, we present novel liquid crystal devices for tailoring the wavefront of optical beams through the Pancharatnam–Berry phase concept. We demonstrate the versatility of these devices by generating an extensive range of optical beams such as beams carrying ±200 units of orbital angular momentum along with Bessel, Airy and Ince–Gauss beams. We characterize both the phase and the polarization properties of the generated beams, confirming our devices' performance.